P92 Systemic alkyl quinolones as novel biomarkers for pulmonary exacerbations in cystic fibrosis: a validation study. (15th November 2016) - Barr, H; Fogarty, A; Halliday, N; Knox, A; Quon, B; Forrester, D; Williams, P; Barrett, D; Camara, M
Abstract : Introduction and objectives: There is a clinical need to identify and validate biomarkers that are sensitive to treatment of infection in cystic fibrosis (CF). The aim of this study was to externally validate two novel biomarkers for pulmonary exacerbations in CF of the alkyl quinolone (AQ) class of quorum sensing molecules produced by Pseudomonas aeruginosa . Methods: Retrospective analysis of 70 plasma samples from thirteen adults with CF obtained during treatment of fifteen discrete exacerbations treated with intravenous antibiotics. Plasma samples were obtained at the start, day five, day ten, at the end of treatment, and at clinical stability. Samples were analysed using liquid chromatography-mass spectrometry. Data were analysed using Spearman's rank correlations and Wilcoxon matched pairs signed-rank tests using STATA 11 statistical software (Texas, USA). Graphs were produced in EXCEL 2011. Results: Plasma 2-heptyl-4-hydroxyquinoline (HHQ) concentration significantly decreased by a median of 221 pmol/L (IQR: 158 to 258 pmol/L) or 73% (IQR 52 to 94%; p = 0.0007) during treatment for a pulmonary exacerbation (Figure 1 ). In the same interval, there was no significant change in plasma NHQ (median decrease of −3 pmol/L; IQR: −35 to 10 pmol/L; p = 0.65). During treatment for a pulmonary exacerbation, percent predicted FEV1 increased by 4% (IQR: 1 to 7%; p = 0.0086). Folloing systemic antimicrobial therapy, systemic IL6 concentration decreased by a median of 2.06 pg/mL (IQR: 1.02 to 3.55 pg/mL; p = 0.0022) and systemic calprotectin decreased by 1687 ng/mL (IQR: 291 to 3992 ng/mL; p = 0.0229). There was no significant association between change in plasma HHQ and change in FEV1 during treatment of a pulmonary exacerbation (Spearman's correlation co-efficient, r = −0.42; p = 0.15). Conclusions: Plasma HHQ declined significantly during treatment of a pulmonary exacerbation and merits further investigation as a biomarker for measuring treatment response in CF. There was no significant decline in plasma NHQ during systemic antimicrobial therapy.